Drivers Of Organizational Innovativeness Among SMEs in Malaysia Halal Industry - Ida Rizyani, Tahir (IJSCH, UK, 2014)
The Malaysia Halal Industry has been one of the lucrative and profitable areas of business in Malaysia with estimated global market value (food and non food) of US$2.1 trillion annually (Industry, 2006). The increasing awareness to select halal products has created a great demand for halal products and services. Malaysia is in a unique spot to become a global halal hub due to its outstanding infrastructure, favourable business atmosphere and well established policies and institutions that support initiatives engaged by the Malaysian Government. Unfortunately, majority of the entrepreneurs (SMEs) are unable to sustain in the market as after three years, the brand name disappear due to innovation, high competition with multinational companies and financial constraints.The main purpose of this paper is to emphasize the drivers of innovativeness in improving business performance among SMEs.Many theorists agreed that the organizational development depends on low or high level of innovativeness. This paper is based on the management behavior towards innovativeness which is crucial for enhancing business performance. It also highlighted the drivers of innovativeness in SMEs Malaysia Halal Industry and a framework for future empirical investigation is proposed.